2020
DOI: 10.1080/07481187.2020.1829746
|View full text |Cite
|
Sign up to set email alerts
|

Personality traits and fears of death and dying predict ageism

Abstract: Ageism, or the discriminative attitudes toward specific age groups, often older adults, is a common prejudice with many negative consequences. This study explored the relationships between personality, fears of death and dying, and subscales of ageism (i.e., Avoidance, Discrimination, and Antilocution). Participants (N ¼ 436) completed measures of personality, death and dying fears, and ageism. Multiple linear regressions showed that agreeableness, openness, and fearing others' death were negatively associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 28 publications
1
13
1
Order By: Relevance
“…Researchers have found that demographic characteristics are significantly associated with ageist attitudes. For instance, individuals who are younger in age (Gellis et al, 2003;Kimuna et al, 2005) and who identify as cisgender men (Boswell, 2012;Chonody et al, 2014;Galton et al, 2020) are more likely to display ageist attitudes. In accordance with the literature, the current study found a significant negative correlation between age and ageist attitudes, and cisgender men scored higher on ageist attitudes compared to cisgender women.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Researchers have found that demographic characteristics are significantly associated with ageist attitudes. For instance, individuals who are younger in age (Gellis et al, 2003;Kimuna et al, 2005) and who identify as cisgender men (Boswell, 2012;Chonody et al, 2014;Galton et al, 2020) are more likely to display ageist attitudes. In accordance with the literature, the current study found a significant negative correlation between age and ageist attitudes, and cisgender men scored higher on ageist attitudes compared to cisgender women.…”
Section: Discussionmentioning
confidence: 99%
“…Terror management theory suggests that ageing anxiety (Allan et al, 2014;Boswell, 2012) and fear of death (Chonody et al, 2014;Galton et al, 2020) are positively associated with ageist attitudes. The results of the current study partially support terror management theory.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations